Lithium-selective adsorbents, methods of making and using the same

CN122999152APending Publication Date: 2026-10-30SHANGHAI XIGU TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510557788.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但现有锂吸附剂对锂离子没有很高的选择性,特别是在沉锂母液这种典型的高钠锂比(Na+/Li+质量比>100)复杂体系中,无法达到选择性吸附、纯化的目的

Benefits of technology

[0011]本发明的锂选择性吸附剂对锂的选择性高,制备简单,使用其进行分离纯化时效果好,绿色环保,成本低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999152A_ABST
    Figure CN122999152A_ABST
Patent Text Reader

Abstract

The present application provides a kind of lithium selective adsorbent and its preparation method and application.The lithium selective adsorbent has the structure shown in formula Ia and / or Ib, wherein M is resin matrix;A is selected from -O-, -NH-(CH2) t - and -NH(CH2) n NH-, n is an integer of 2-9, t is an integer of 0-9;D1 is a compound containing 1-3 six-membered aromatic rings with hydroxyl at the ortho position of C=O, the number of nitrogen atoms in the ring is ≥1;D2 is a compound containing 1-3 six-membered aromatic rings with hydroxyl at the ortho position of SO2, the number of nitrogen atoms in the ring is 0-2.The lithium selective adsorbent of the present application improves the selectivity of lithium, which can effectively separate lithium from sodium.(Formula Ia) (Formula Ib)
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic synthesis technology, specifically to a lithium selective adsorbent, its preparation method, and its application. Background Technology

[0002] In lithium carbonate production, whether it is salt lake brine or ore lithium extraction process, lithium carbonate is ultimately obtained by sodium carbonate precipitation. However, 0.5-2 g / L of lithium ions remain in the lithium precipitation mother liquor, and it is necessary to recover and reuse this part of lithium. Traditional precipitation method has low lithium recovery rate, and subsequent purification requires repeated pH adjustment or secondary precipitation, resulting in high production cost.

[0003] Compared with traditional methods, resin solid-phase extraction has advantages such as no emulsification, low loss, simple operation, and low pollution. However, existing lithium adsorbents do not have high selectivity for lithium ions, especially in lithium precipitation mother liquor, which typically has a high sodium-to-lithium ratio (Na₂O₃ / Na₂O₃). + / Li + In complex systems with a mass ratio > 100, selective adsorption and purification cannot be achieved.

[0004] Therefore, it is necessary to develop a selective lithium adsorbent that can be used in lithium-sodium solutions, especially in Na+ solutions. + / Li + Effective separation of lithium is achieved in a high-sodium system with a mass ratio >100. Summary of the Invention

[0005] One object of the present invention is to provide a novel adsorbent that has high selectivity for lithium and can be used for the separation and extraction of lithium from lithium-sodium solutions.

[0006] Therefore, according to a first aspect, the present invention provides a lithium selective adsorbent, characterized in that it has the structure shown in formula Ia and / or Ib: (Formula Ia), (Formula Ib), in: M is the resin matrix; A is selected from -O- and -NH-(CH2). t - and -NH(CH2) n NH-, where n is an integer from 2 to 9, and t is an integer from 0 to 9; D1 is a compound containing 1-3 six-membered aromatic rings with a hydroxyl group at the C=O ortho position, and the number of nitrogen atoms in the ring is ≥1; D2 is a compound containing 1-3 six-membered aromatic rings with a hydroxyl group at the ortho position of SO2, and 0-2 nitrogen atoms in the rings; The hydrogens on the six-membered aromatic ring, other than the phenolic hydroxyl hydrogen, are optionally surrounded by one or more hydrogens selected from C1-C2. 20Alkyl, C1-C 20 Alkoxy, C6-C 12 Aryl, optional C1-C 20 Substitution of amino, hydroxyl, fluorine and chlorine atoms by substituted groups.

[0007] According to a second aspect, the present invention provides a method for preparing the above-mentioned lithium selective adsorbent, characterized in that it includes one of the following steps S1, S2, S3, S4, and S5: S1. A resin containing a primary amine group is reacted with a compound of formula IIa or IIb in the presence of a catalyst at a temperature of 40-120°C via an amine-ester exchange reaction to obtain the lithium-selective adsorbent. (Formula IIa) (Equation IIb) in: Y is C1-C 10 alkoxy groups; D1 and D2 are defined as for equation Ia or Ib. S2. In an acidic solution in the presence of aldehydes, a resin containing a primary amine group is reacted with a ketone of formula IIIa or IIIb at a temperature of 40-120°C to obtain the lithium-selective adsorbent. (Formula IIIa) (Equation IIIb) in: D1 and D2 are defined as for equation Ia or Ib. S3, First, add H2N-(CH2) n -NH2 undergoes an amine transesterification reaction with a compound of formula IIa or IIb to obtain an intermediate of formula IVa or IVb. The intermediate of formula IVa or IVb is then reacted with a chlorinated resin to obtain the lithium-selective adsorbent, wherein the compound having formula IIa or IIb is as defined for step S1. (Formula IVa) (Formula IVb) in: n is defined for equation I. D1 and D2 are defined as for equation Ia or Ib. S4. Add alkaline solution to the reaction vessel containing the swollen chlorine bead resin, heat to induce a hydrolysis reaction, separate the resin after the reaction, wash repeatedly with solvent to obtain the hydrolyzed chlorine beads, place the hydrolyzed chlorine bead resin in a reaction vessel, add a solvent to swell the chlorine bead resin, a compound of formula IIa or IIb, an acid-binding agent, and a co-catalyst, heat under reflux to induce a substitution reaction, and obtain the lithium selective adsorbent, wherein the compound of formula IIa or IIb is as defined in step S1. S5. A substitution reaction is carried out between a resin containing a primary amine group and a compound of formula Va or Vb in an alkaline solution under heating conditions to obtain the lithium-selective adsorbent. (Equation Va) (Formula Vb) in: X is either Cl or Br; q is an integer from 1 to 9, preferably q is 0, 1 or 2; D1, as defined with respect to formula Ia, is a compound containing 1-3 six-membered aromatic rings with C1-C8 alkoxy groups at the C=O ortho position, and the number of nitrogen atoms in the ring is ≥1. D2, as defined with respect to formula Ib, is a compound containing 1-3 six-membered aromatic rings with C1-C8 alkoxy groups at the ortho position of SO2, and the number of nitrogen atoms in the rings is 0-2. When D1 and D2 are not as defined for formula Ia or formula Ib, step S5 further includes adding a hydrolysis step after the substitution reaction.

[0008] According to a third aspect, the present invention provides the use of the above-mentioned lithium selective adsorbent for adsorbing lithium.

[0009] According to a fourth aspect, the present invention provides an extractant for solid-phase extraction of lithium, characterized in that it contains the above-mentioned lithium-selective adsorbent.

[0010] According to a fifth aspect, the present invention provides a method for extracting lithium from high-sodium brine, characterized in that an extractant containing the above-mentioned lithium selective adsorbent is used, and the initial aqueous phase pH is controlled to be 9-13.5.

[0011] The lithium selective adsorbent of the present invention has high selectivity for lithium, is simple to prepare, has good separation and purification effect, is green and environmentally friendly, and has low cost. Detailed Implementation

[0012] The various aspects of the invention, as well as further objects, features and advantages, will be described in more detail below.

[0013] Lithium selective adsorbent According to a first aspect, the present invention provides a lithium selective adsorbent, characterized in that it has the structure shown in formula Ia and / or Ib: (Formula Ia), (Formula Ib), in: M is the resin matrix; A is selected from -O- and -NH-(CH2). t - and -NH(CH2) n NH-, where n is an integer from 2 to 9, and t is an integer from 0 to 9; D1 is a compound containing 1-3 six-membered aromatic rings with a hydroxyl group at the C=O ortho position, and the number of nitrogen atoms in the ring is ≥1; D2 is a compound containing 1-3 six-membered aromatic rings with a hydroxyl group at the ortho position of SO2, and 0-2 nitrogen atoms in the rings; The hydrogens on the six-membered aromatic ring, other than the phenolic hydroxyl hydrogen, are optionally surrounded by one or more hydrogens selected from C1-C2. 20 Alkyl, C6-C 12 Aryl, optional C1-C 20 Substitution of amino, hydroxyl, fluorine and chlorine atoms by substituted groups.

[0014] The present invention does not specifically limit the resin matrix M. Preferably, the resin matrix M is selected from polystyrene resin, copolymer of styrene and divinylbenzene, phenolic resin, polyacrylic acid resin, and silicone resin. More preferably, the resin matrix M is selected from polystyrene resin and copolymer of styrene and divinylbenzene.

[0015] Preferably, D1 is a compound containing 1-2 six-membered aromatic rings with a hydroxyl group at the C=O ortho position, and the number of nitrogen atoms in the ring is 1 or 2.

[0016] Preferably, D2 is a compound containing 1-2 hexa-membered aromatic molecules with a hydroxyl group at the ortho position of SO2. The number of nitrogen atoms in the ring is 0, 1, or 2.

[0017] Preferably, the hydrogen atoms on the six-membered aromatic ring, other than the phenolic hydroxyl hydrogen, are optionally substituted by one or two groups selected from C1-C8 alkyl, C1-C8 alkoxy, phenyl, optionally C1-C8 substituted amino, hydroxyl, fluorine and chlorine atoms.

[0018] Specifically, n is 2, 3, 4, 5, 6, 7, 8 or 9, and t is 1, 2, 3, 4, 5, 6, 7, 8 or 9, preferably n is 2 and t is 0, 1 or 2.

[0019] Preferably, D1 has the following structure: , , , , , , , , , , , D2 has the following structure: , , , , , , , , , , , , , * indicates a connection site.

[0020] More preferably, D1 has the following structure: , , , , and , D2 has the following structure: and , * indicates a connection site.

[0021] Preferably, the lithium selective adsorbent has a structure selected from the following: , , , , , , , , , , , , , , , , , , , , , , , , and , M is selected from polystyrene resin, copolymer of styrene and divinylbenzene, phenolic resin, polyacrylic resin and silicone resin.

[0022] More preferably, the lithium selective adsorbent has a structure selected from the following: , , , , , , and , M is selected from polystyrene resin and copolymers of styrene and divinylbenzene.

[0023] The lithium-selective adsorbent obtained according to the present invention has high selectivity for lithium and adsorbs lithium element in lithium-sodium solution, providing a new extractant for extraction and purification processes.

[0024] Method for preparing the above-mentioned lithium selective adsorbent According to a second aspect, the present invention provides a method for preparing the above-mentioned lithium selective adsorbent, characterized in that it includes one of the following steps S1, S2, S3, S4, and S5: S1. A resin containing a primary amine group is reacted with a compound of formula IIa or IIb in the presence of a catalyst at a temperature of 40-120°C via an amine-ester exchange reaction to obtain the lithium-selective adsorbent. (Formula IIa) (Equation IIb) in: Y is C1-C 10 alkoxy groups; D1 and D2 are defined as for equation Ia or Ib. S2. In an acidic solution in the presence of aldehydes, a resin containing a primary amine group is reacted with a ketone of formula IIIa or IIIb at a temperature of 40-120°C to obtain the lithium-selective adsorbent. (Formula IIIa) (Equation IIIb) in: D1 and D2 are defined as for equation Ia or Ib. S3, First, add H2N-(CH2) n -NH2 undergoes an amine transesterification reaction with a compound of formula IIa or IIb to obtain an intermediate of formula IVa or IVb. The intermediate of formula IVa or IVb is then reacted with a chlorinated resin to obtain the lithium-selective adsorbent, wherein the compound of formula IIa or IIb is as defined in step S1. (Formula IVa) (Formula IVb) in: n is defined for equation I. D1 and D2 are defined as for equation Ia or Ib. S4. Add alkaline solution to the reaction vessel containing the swollen chlorine bead resin, heat to induce a hydrolysis reaction, separate the resin after the reaction, wash repeatedly with solvent to obtain the hydrolyzed chlorine beads, place the hydrolyzed chlorine bead resin in a reaction vessel, add a solvent to swell the chlorine bead resin, a compound of formula IIa or IIb, an acid-binding agent, and a co-catalyst, heat under reflux to induce a substitution reaction, and obtain the lithium selective adsorbent, wherein the compound of formula IIa or IIb is as defined in step S1. S5. A substitution reaction is carried out between a resin containing a primary amine group and a compound of formula Va or Vb in an alkaline solution under heating conditions to obtain the lithium-selective adsorbent. (Equation Va) (Formula Vb) in: X is either Cl or Br; q is an integer from 1 to 9, preferably q is 0, 1 or 2; D1, as defined with respect to formula Ia, is a compound containing 1-3 six-membered aromatic rings with C1-C8 alkoxy groups at the C=O ortho position, and the number of nitrogen atoms in the ring is ≥1. D2, as defined with respect to formula Ib, is a compound containing 1-3 six-membered aromatic rings with C1-C8 alkoxy groups at the ortho position of SO2, and the number of nitrogen atoms in the rings is 0-2. When D1 and D2 are not as defined for formula Ia or formula Ib, step S5 further includes adding a hydrolysis step after the substitution reaction.

[0025] Before steps S1, S2, S3, S4, and S5, the resin matrix can be pretreated.

[0026] Specifically, the pretreatment includes rinsing the resin matrix with a solvent, stirring and shaking the resin, and then removing excess solvent.

[0027] Preferably, the solvent used in the pretreatment is a mixture of one or more solvents selected from water, ethanol, diethyl ether, toluene, dioxane, N,N-dimethylformamide, dichloromethane, and ethyl acetate.

[0028] In some embodiments, the preparation method includes step S1.

[0029] Preferably, the compound of formula IIa is selected from... 2-Hydroxynicotinic acid methyl ester, 4-hydroxy-5-pyrimidinecarboxylate methyl ester, 3-hydroxy-2-pyridinecarboxylate methyl ester, 4-hydroxyquinoline-3-carboxylate ethyl ester, 2,4-dihydroxyquinoline-3-carboxylate ethyl ester, 6,8-difluoro-4-hydroxyquinoline-3-carboxylate ethyl ester, 4-hydroxy-6,8-dimethylquinoline-3-carboxylate ethyl ester.

[0030] Preferably, the compound of formula IIb is selected from... (CAS: 2835425-91-5) or (CAS: 37874-08-1).

[0031] More preferably, the compound of formula IIa is selected from... 2-Hydroxynicotinic acid methyl ester, 4-hydroxy-5-pyrimidinecarboxylate methyl ester, 4-hydroxyquinoline-3-carboxylate ethyl ester, 2,4-dihydroxyquinoline-3-carboxylate ethyl ester or 6,8-difluoro-4-hydroxyquinoline-3-carboxylate ethyl ester.

[0032] Preferably, the catalyst is 4-dimethylaminopyridine.

[0033] Preferably, the molar ratio of the primary amine group, compound of formula IIa or IIb of the resin matrix to the catalyst is 1:(1-1.5):(0.1-0.5).

[0034] Preferably, the amine-ester exchange reaction is carried out in a solvent selected from one or more solvents chosen from methanol, ethanol, diethyl ether, toluene, dioxane, N,N-dimethylformamide, dichloromethane, and ethyl acetate.

[0035] Preferably, the amount of solvent used in the amine transesterification reaction is 1-30 times the mass of the resin.

[0036] Preferably, the amine-lipid exchange reaction is carried out at a temperature in the range of 60-120°C.

[0037] Preferably, the time for the amine-lipid exchange reaction is 2-48 hours.

[0038] In some embodiments, the preparation method includes step S2.

[0039] Preferably, in step S2, the acid in the acidic solution is one or a mixture of sulfuric acid, hydrochloric acid, nitric acid, phosphoric acid, and perchloric acid.

[0040] Preferably, in step S2, the solvent in the acidic solution is one or a mixture of water, ethanol, methanol, and N,N-dimethylformamide.

[0041] Preferably, in step S2, the concentration of the acidic solution is 0.1-6 mol / L.

[0042] Preferably, in step S2, the aldehyde is any one or a mixture of formaldehyde, benzaldehyde, and C1-C9 alkyl formaldehyde.

[0043] More preferably, in step S2, the aldehyde is any one or a mixture of formaldehyde, acetaldehyde, propionaldehyde, and benzaldehyde.

[0044] More preferably, in step S2, the aldehyde is selected from formaldehyde.

[0045] Preferably, the ketone of formula IIIa is selected from 1-(4-hydroxy-3-pyridyl)ethyl ketone, 2-hydroxy-3-acetylpyridine, (CAS: 1539134-54-7), 1-(3-hydroxypyridin-2-yl) ethyl ketone or 3-acetyl-1,6-naphthidium-2(1H)-one.

[0046] Preferably, the ratio of the amount of acid in the acidic solution to the molar amount of primary amine groups in the resin is 0.5-3:1.

[0047] Preferably, the molar ratio of the primary amine groups, aldehydes and ketones of formula IIIa or IIIb in the resin matrix is ​​1:1-1.5:0.75-1.75, more preferably 1:1-1.25:0.8-1.5.

[0048] Preferably, the amount of solvent in the acidic solution is 1-30 times the mass of the resin.

[0049] Preferably, in step S2, the reaction time is 4-48 hours.

[0050] In some embodiments, the preparation method includes step S3.

[0051] Preferably, the solvent, temperature, and time for the amine-lipid exchange reaction in step S3 are as described in step S1.

[0052] Preferably, the molar ratio of H2N-(CH2)n-NH2 to the compound of formula IIa or IIb is 1.1-1.5:1.

[0053] The "chloro-2-methyl resin" mentioned in this application refers to a resin containing a chloromethyl (-CH2Cl) functional group.

[0054] Preferably, the reaction in step S3 is carried out in an alkaline solution at a temperature of 40-120°C.

[0055] Preferably, the solute in the alkaline solution in step S3 is one or a combination of two or more of sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate, sodium bicarbonate, ammonia, triethylamine, and calcium hydroxide.

[0056] Preferably, the solvent of the alkaline solution in step S3 is one or a combination of two or more of water, ethanol, methanol, and N,N-dimethylformamide.

[0057] Preferably, the concentration of the alkaline solution in step S3 is 0.1-5 mol / L.

[0058] The molar ratio of the chlorinated resin and the substance of formula IVa or IVb mentioned in step S3 is 1:(1.2-3).

[0059] Preferably, the amount of solvent used in the alkaline solution in step S3 is 1-30 times the mass of the resin.

[0060] Preferably, the reaction time in step S3 is 4-48 hours.

[0061] In some embodiments, the preparation method includes step S4.

[0062] Preferably, the solvent used to swell the chloroform resin in step S4 is any one of acetone, ethanol, 1,4-dioxane, dichloromethane, dimethyl sulfoxide, N,N-dimethylformamide, benzene, and diethyl ether.

[0063] More preferably, the solvent is acetone.

[0064] Preferably, the swelling time in step S4 is 6-12 hours, and more preferably 10 hours.

[0065] Preferably, the solvent used for washing in the hydrolysis reaction described in step S4 is any one or a mixture of several of anhydrous ethanol, dichloromethane, methanol, n-hexane, deionized water, 1,4-dioxane, and acetone, with anhydrous ethanol and acetone being the most preferred.

[0066] Preferably, the alkaline solution in step S4 is either a sodium hydroxide solution or a potassium hydroxide solution, and more preferably, the alkaline solution is a sodium hydroxide solution.

[0067] Preferably, the concentration of the sodium hydroxide solution or potassium hydroxide solution in step S4 is 1-4 mol / L, more preferably 2-3 mol / L.

[0068] Preferably, the hydrolysis reaction in step S4 is carried out at a temperature of 40-90°C for 8-24 hours; more preferably, the temperature is 50°C and the reaction time is 12 hours.

[0069] Preferably, the acid-binding agent in step S4 is any one of potassium carbonate, sodium carbonate, triethylamine, tri-n-propylamine, and N,N-diisopropylethylamine.

[0070] Potassium carbonate is the preferred acid-binding agent.

[0071] Preferably, the co-catalyst in step S4 includes potassium iodide and / or tetrabutylammonium chloride.

[0072] Preferably, the molar ratio of the chlorinated resin, the compound of formula IIa or IIb, and the acid-binding agent in step S4 is 1:(1.5-3):(1-2).

[0073] More preferably, the feeding ratio is 1:2:1.5.

[0074] Preferably, the amounts of potassium iodide and tetrabutylammonium chloride are both catalyst equivalents.

[0075] Preferably, the substitution reaction in step S4 is carried out at a reaction temperature of 60-100°C for 8-24 hours; more preferably, the temperature is 80°C and the reaction time is 12 hours.

[0076] In some embodiments, the preparation method includes step S5.

[0077] Preferably, the solute, solvent, and concentration of the alkaline solution in step S5 are as described with respect to step S3.

[0078] Preferably, the ratio of the amount of solute in the alkaline solution to the molar amount of primary amine groups in the resin in step S5 is 0.8-2.5:1.

[0079] Preferably, the ratio of the content of primary amine groups in the resin to the molar amount of the compound of formula Va or Vb in step S5 is 1:0.75-1.75, more preferably 1:0.8-1.5.

[0080] Preferably, the amount of solvent and the reaction time in step S5 are as described for step S3.

[0081] Preferably, the hydrolysis reaction in step S5 is as described in step S4.

[0082] Preferably, the preparation method includes washing the lithium selective adsorbent with anhydrous ethanol and / or acetone.

[0083] Preferably, the resin matrix is ​​a macroporous resin.

[0084] As used herein, the pore size of the macroporous resin is in the range of 10-1000 nm, preferably 20-100 nm.

[0085] The preparation method of the present invention can effectively prepare the lithium selective adsorbent of the present invention.

[0086] Applications of lithium selective adsorbents for lithium adsorption According to a third aspect, the present invention provides the use of the above-mentioned lithium selective adsorbent for adsorbing lithium.

[0087] The lithium selective adsorbent can be used to adsorb lithium in hydrometallurgy and environmental protection industries.

[0088] According to a fourth aspect, the present invention provides an extractant for solid-phase extraction of lithium, characterized in that it contains the above-mentioned lithium selective adsorbent.

[0089] According to a fifth aspect, the present invention provides a method for extracting lithium from high-sodium brine, characterized in that an extractant containing the above-mentioned lithium selective adsorbent is used, and the initial aqueous phase pH is controlled to be 9-13.5, preferably 10-13.5, and more preferably 11-13.

[0090] The lithium selective adsorbent of the present invention can effectively adsorb lithium.

[0091] In some implementations, the method includes the following steps: S11: The above lithium selective adsorbent is contacted with a lithium- and sodium-containing solution for extraction, and then solid-liquid separation is performed to obtain lithium-loaded lithium selective adsorbent and raffinate. S12: The lithium-selective adsorbent loaded with lithium is back-extracted using an acid solution and then subjected to solid-liquid separation to obtain the back-extracted adsorbent and the lithium back-extracting solution.

[0092] Advantageously, the lithium-containing sodium solution contains 0.1-5 g / L of lithium and 0.1-120 g / L of sodium, with a sodium-to-lithium ratio ≤500:1.

[0093] Advantageously, the extraction time is 1 min or more, for example 1-120 min, for example 5-100 min, for example 10-80 min, preferably 10-60 min.

[0094] Advantageously, the lithium-loaded lithium selective adsorbent is washed with water before back-extraction to remove sodium.

[0095] Advantageously, the acid solutions used in the back-extraction are each independently selected from sulfuric acid solution and / or hydrochloric acid solution. Preferably, the concentration of the sulfuric acid solution used in the back-extraction is 0.5-6 mol / L and the concentration of the hydrochloric acid solution is 1-8 mol / L.

[0096] In some embodiments, the method further includes pretreatment of the lithium selective adsorbent, namely, mixing the lithium selective adsorbent with a 1-2 mol / L sulfuric acid or hydrochloric acid solution and stirring, then washing with pure water until the supernatant is colorless, then washing with a 0.2-1 mol / L, preferably 0.2-0.5 mol / L sodium hydroxide or potassium hydroxide solution until the supernatant is alkaline, then washing the resin with pure water until neutral, and filtering to obtain the pretreated resin for use.

[0097] The lithium selective adsorbent of this invention operates in an alkaline environment with a pH of 9-13.5, preferably 10-13.5, in Na+. + / Li + Achieving a mass ratio within the range of 10-500:1: when Na + / Li + When the mass ratio is >100:1, the lithium-sodium separation coefficient βLi / Na ≥15.0; Na + / Li + When the mass ratio is 10-100:1, the lithium-sodium separation coefficient is ≥18.0.

[0098] The lithium-selective adsorbent of the present invention improves the selectivity for lithium, and can effectively separate lithium from sodium.

[0099] The "selectivity" mentioned in this application refers to the separation coefficient of the metallic elements. β Furthermore, the separation coefficient is derived from the following formula: β A / B =D A / D B In the formula, D A This represents the ratio of the content of metal element A in the resin to the content of metal element A in the raffinate aqueous phase after one extraction. D B This represents the ratio of the content of metal element B in the resin to the content of metal element B in the raffinate aqueous phase after one extraction.

[0100] In this application, the terms "comprising" and "including" cover situations where other elements not explicitly mentioned are also included, as well as situations where the mentioned elements constitute the entirety of the application.

[0101] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In the event of any discrepancy between the definitions of terms in this specification and their commonly understood meaning by one of ordinary skill in the art to which this invention pertains, the definitions set forth herein shall prevail.

[0102] Unless otherwise stated, all numerical values ​​for the amount of ingredients, temperature, time, etc., used in the specification and claims are to be understood as being modified by the term "about". Therefore, unless otherwise indicated, the numerical parameters set forth herein are approximate values ​​that can be varied to obtain the desired performance.

[0103] Example The following will further illustrate the concept and technical effects of the present invention with reference to embodiments, so that those skilled in the art can fully understand the purpose, features, and effects of the present invention. It will be readily understood by those skilled in the art that the embodiments described herein are merely illustrative, and the scope of the present invention is not limited thereto.

[0104] Example 1: Preparation of Resin 1 The synthetic route for resin 1 is shown below: (Resin 1) Add 10 g (30 mmol, -NH2) of primary amine polystyrene resin (from Samsung Resins, model SX382) and 5.4 g (35 mmol) of... to a three-necked flask. (CAS No.: 67367-24-2), 0.48 g (4 mmol) of 4-dimethylaminopyridine, and 50 mL of N,N-dimethylformamide were added. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 1.

[0105] Example 2: Preparation of Resin 2 The synthetic route for resin 2 is shown below: (Resin 2) Add 5.2g of ethylenediamine and 11.0g (72mmol) of [unspecified ingredient] to a three-necked flask. 0.96 g (8 mmol) of 4-dimethylaminopyridine was added, followed by 100 mL of N,N-dimethylformamide. The mixture was heated at 80 °C for 8 hours under mechanical stirring to obtain... Intermediate.

[0106] Then take 10 g (50 mmol) of intermediate and chlorinated polymethyl ether resin (the preparation method of chlorinated polymethyl ether resin is described in CN101781379B, purchased from Zhejiang Zhengguang Industrial Co., Ltd.) were placed in a 100 ml three-necked flask, and 60 g of N,N-dimethylformamide and 7.27 g (72 mmol) of triethylamine were added sequentially. The mixture was heated to 50 °C under mechanical stirring and reacted for 8 hours. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 2.

[0107] Example 3: Preparation of Resin 3 The synthetic route for resin 3 is shown below: (Resin 3) 10 g (30 mmol, -NH2) of primary amine polystyrene resin (from Samsung Resin, model SX382), 7.6 g (35 mmol) of ethyl 4-hydroxyquinoline-3-carboxylate, and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask, followed by 50 mL of toluene. The mixture was heated to 80 °C for 24 hours under mechanical stirring. After the reaction was completed, the resin was separated and repeatedly washed with anhydrous ethanol and acetone to obtain resin 3.

[0108] Example 4: Preparation of Resin 4 The synthetic route for resin 4 is shown below: (Resin 4) 10 g (30 mmol, -NH2) of primary amine polystyrene resin (from Samsung Resin, model SX382), 5.4 g (35 mmol) of methyl 4-hydroxy-5-pyrimidinecarboxylate, and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask. Then, 100 mL of N,N-dimethylformamide was added. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 4.

[0109] Example 5 The synthetic route for resin 5 is shown below: (Resin 5) 10 g (30 mmol, -NH2) of primary amine polystyrene resin (from Samsung Resin, model SX382), 8.9 g (35 mmol) of ethyl 6,8-difluoro-4-hydroxyquinoline-3-carboxylate, and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask. Then, 100 mL of N,N-dimethylformamide was added. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 5.

[0110] Example 6 The synthetic route for resin 6 is shown below: (Resin 6) In a 250 mL three-necked flask, 30 g of chlorinated resin was added and swollen thoroughly with 100 mL of dichloromethane for 12 h. Then, the swollen chlorinated resin was transferred to another 250 mL three-necked flask, and 100 mL of 2 mol / L sodium hydroxide solution was added. The mixture was reacted at 50 °C for 12 h. After the reaction was completed, the resin was separated and washed twice with 100 mL of anhydrous ethanol to obtain the hydrolyzed chlorinated resin.

[0111] The hydrolyzed chlorine bulbs were placed in a 250 mL three-necked flask, and 100 mL of anhydrous ethanol was added. Then, 21.9 g of methyl 2,4-dihydroxyquinoline-3-carboxylic acid was added sequentially. 6.22 g of anhydrous potassium carbonate, 0.2 g of potassium iodide, and 1 drop of tetrabutylammonium chloride were added and refluxed for 12 h. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 6.

[0112] Example 7 The synthetic route for resin 7 is shown below: (Resin 7) Specifically, 10 g (30 mmol, -NH2) and 9.3 g (45 mmol) of primary amino polystyrene microspheres (from Samsung Resin, model SX382) were taken. (CAS No.: 219715-44-3) was placed in a 100ml three-necked flask, and 57g of acetone and 4.6g (45mmol) of triethylamine were added in sequence. The mixture was heated to 60℃ under mechanical stirring and reacted for 4 hours. After the reaction was completed, the resin was separated and boiled at 50℃ for 12 hours with 2 mol / L NaOH solution. Then it was washed repeatedly with anhydrous ethanol and acetone to obtain resin 7.

[0113] Example 8 The synthetic route for resin 8 is shown below: (Resin 8) Add 10g (30mmol, -NH2) primary amine polystyrene resin (from Samsung Resins, model SX382) and 7.1g (35mmol) of [unclear text - likely a continuation of a previous sentence] to a three-necked flask. 0.48 g (4 mmol) of 4-dimethylaminopyridine was added, followed by 100 mL of N,N-dimethylformamide. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and repeatedly washed with anhydrous ethanol and acetone to obtain resin 8.

[0114] Example 9 The properties of the resin obtained above were tested as described below: Pretreatment: The resin was mixed with 2 mol / L sulfuric acid and stirred at 250 rpm for 30 min. It was then washed with pure water until the supernatant was colorless. After that, it was washed with 0.25 mol / L sodium hydroxide solution until the supernatant was alkaline. The resin was then washed with pure water until it was neutral. The pretreated resin was then filtered for later use. The mixture contains 0.1 g / L Li and 40 g / L Na (Na + / Li +Sulfate solutions with a mass ratio of 400:1 and pH values ​​of 10, 11, 12, 13, and 13.5 were used as the initial aqueous phase. Then, 30 mL of the initial aqueous phase was mixed with 10 g of pretreated resin and shaken at room temperature for 60 min. After extraction, solid-liquid separation was performed to obtain the raffinate aqueous phase and the lithium-loaded resin. The concentration of each metal element in the raffinate aqueous phase was determined by inductively coupled plasma atomic emission spectrometry (ICP). The content of each metal element in the lithium-loaded resin was determined by the difference method. The results are summarized in Table 1.

[0115] Table 1. Metal element content and separation coefficient in the raffinate of each resin As shown in Table 1, within the pH range of 10-13.5, based on an initial Li concentration of 0.1 g / L, the lithium adsorption rate reached 58%-81%, and the Li / Na separation coefficient remained stable between 17.8-36.3. Specifically, at pH 12 and Na... + / Li + Under conditions where the mass ratio is >100:1, the lithium-sodium separation coefficient βLi / Na ≥25.0. Each resin exhibits specific selectivity for lithium within the pH range of 10-13.5, making them suitable for the selective adsorption and separation of lithium in low-lithium, high-sodium solutions.

[0116] The resin was back-extracted three times with 30 mL of 2.5 mol / L hydrochloric acid solution, 10 mL each time, to separate the solid and liquid phases and obtain the back-extracted resin.

[0117] Example 10 The properties of the back-extraction resin in Example 9 were tested as described below: The back-extracted resin described in Example 9 was washed three times with 30 mL of pure water, and then washed with 0.25 mol / L sodium hydroxide solution until the supernatant was alkaline. After that, it was washed with pure water until it was neutral to obtain the regenerated resin after transformation for later use.

[0118] A sulfate solution containing 3.5 g / L Li and with a pH of 12 was prepared as the initial aqueous phase. 2 g of the regenerated resin after transformation was placed in each beaker, and 60 mL of the prepared initial aqueous phase was added. The mixture was shaken and extracted at room temperature for 60 min. After extraction, solid-liquid separation was performed to obtain the raffinate aqueous phase. The lithium concentration in the raffinate aqueous phase was determined by inductively coupled plasma atomic emission spectrometry (ICP). The lithium content in the back-extracted resin was calculated using the difference method to obtain the lithium loading of the back-extracted resin. The results are summarized in Table 2.

[0119] Table 2. Lithium loading of the resin after back-extraction As shown in Table 2, the lithium loading of each resin after back-extraction and regeneration ranged from 6.9 to 7.4 mg / g, indicating that the lithium loading of the resin is ≥6.5 mg / g under pH=12 conditions. After 10 cycles, the loading did not decrease significantly, indicating that the resin has excellent regeneration stability.

[0120] Example 11 The test was conducted according to Example 9, except that the Li concentration was 0.1 g / L, and the Na ion concentrations were changed to 1 g, 2 g / L, 5 g / L, and 10 g / L, with a pH of 12 in each case, as the initial aqueous phase. 30 mL of the initial aqueous phase was mixed with 10 g of the pretreated resin and shaken at room temperature for 60 min. The test results are summarized in Table 3.

[0121] Table 3. Performance data of resin 4 under different sodium-lithium ratios As shown in Table 3, in Na + / Li + Within a mass ratio range of 10:1 to 100:1, the lithium adsorption rate remained stable between 78% and 85%, and the βLi / Na ratio remained in a high selectivity range of 37.2 to 63.4. This example confirms that the adsorbent exhibits high selectivity over a wide range of Na... + / Li + Excellent performance is maintained at mass ratios (10:1-100:1).

[0122] Comparative Example 1 Resin 9 was prepared according to the following synthetic route: (Resin 9) 10 g of primary amine polystyrene resin (from Samsung Resin, model SX382), 5.3 g (35 mmol) of methyl salicylate, and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask. Then, 100 mL of N,N-dimethylformamide was added. The mixture was heated at 100 °C for 12 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 9.

[0123] The test was conducted according to Example 9, except that the initial aqueous phase pH values ​​were 9, 10, 11, 12, and 13, and the resin structural formula was [insert structural formula here]. M represents polystyrene microspheres, i.e., resin 9.

[0124] The results showed that when the initial aqueous phase pH values ​​were 9, 10, 11, 12, and 13, the lithium concentrations in the raffinate were 0.053 g / L, 0.048 g / L, 0.042 g / L, 0.031 g / L, and 0.027 g / L, respectively, and the sodium concentrations were 37.0 g / L, 37.0 g / L, 36.6, 36.4 g / L, and 36.1 g / L, respectively. The separation coefficients of resin 9 for lithium and sodium were poor, at 11.0, 13.4, 14.9, 22.5, and 25.0, respectively, which were significantly lower than the β value of the resin described in Example 9 under the same pH conditions.

[0125] Comparative Example 2 Resin 10 was prepared according to the following synthetic route: (Resin 10) 10 g of primary amine polystyrene resin (from Samsung Resin, model SX382), 4.1 g (35 mmol) of methyl acetoacetate and 0.48 g (4 mmol) of 4-dimethylaminopyridine were added to a three-necked flask, followed by 100 mL of N,N-dimethylformamide. The mixture was heated to 80 °C for 24 hours under mechanical stirring. After the reaction was completed, the resin was separated and washed repeatedly with anhydrous ethanol and acetone to obtain resin 10.

[0126] The test was conducted according to Example 9, except that the initial aqueous phase pH was 11, 12, and 13, and the resin's structural formula was [insert structural formula here]. M represents polystyrene microspheres, i.e., resin 10.

[0127] The results showed that when the initial aqueous phase pH was 11, 12, and 13, the lithium concentration in the raffinate was 0.089, 0.084 g / L, and 0.078 g / L, respectively, and the sodium concentration was 36.8 g / L, 36.5 g / L, and 36.3 g / L, respectively. The separation coefficients of Resin 10 for lithium and sodium were poor, at 1.4, 2.0, and 2.8, respectively, indicating poor separation of lithium and sodium.

[0128] Comparative Example 3 Resin 1 was tested according to Example 9, except that the initial aqueous phase pH value was 9.

[0129] The results showed that when the lithium concentration in the raffinate was 0.044 g / L and the sodium concentration was 37.0 g / L, the selectivity coefficients of resin 1 for lithium and sodium were 15.8. At pH=9, the β value (15.8) of the resin of the present invention still met the industrial grade requirements (β≥15), while the β value of comparative example 1 was 11.0 under the same conditions, proving that the present invention has a better separation effect of lithium and sodium at a lower pH value.

[0130] Comparative Example 4 The first component is 2-hydroxy-4-n-octyloxybenzophenone, with an addition amount of 0.05 mol; the second component is sulfonated kerosene, with an addition amount of 1 liter. After mixing until homogeneous, it is used as the organic phase for lithium extraction.

[0131] The organic phase used for lithium extraction was tested according to Example 10. The difference from Example 10 was that the initial pH of the aqueous phase was 9, 10, 11, 12, and 13. The extraction operation conditions were: 20 mL of organic phase, 20 mL of aqueous phase, O / A ratio of 1:1, room temperature, in a separatory funnel, shaken for 60 minutes, phase separation for 10 minutes, and the remaining extract was used for ion concentration analysis.

[0132] The results showed that the lithium concentrations in the raffinate were 0.074, 0.069 g / L, 0.053 g / L, 0.044 g / L, and 0.032 g / L, respectively, and the sodium concentrations were 35.7 g / L, 35.2 g / L, 34.4 g / L, 33.2 g / L, and 32.8 g / L, respectively. The lithium / sodium separation coefficients βLi / Na were 2.9, 3.3, 5.4, 6.2, and 9.5, respectively. Even at the optimal pH of 13, the conventional extractant had a β(Li / Na) value of 9.5, which was significantly lower than the β value of the resin of this invention under the same pH conditions.

[0133] The lithium-loaded organic phase was back-extracted with 2.5 mol / L hydrochloric acid solution and reused. After 10 cycles, under the condition of an initial pH of 9, the separation coefficient of the organic phase for lithium / sodium in this embodiment decreased from the initial 2.9 to 2.4. Under the same conditions (pH=9), the separation coefficient of resin 1 of the present invention decreased from 15.8 to 15.3, which shows that the resin of the present invention is more stable than organic solvents.

[0134] The foregoing descriptions are merely exemplary embodiments or examples of the present invention and are not intended to limit the invention. Those skilled in the art will recognize that the present invention can be modified and varied in many ways. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principle of the present invention are included within the scope of the claims of this application.

Claims

1. A lithium-selective adsorbent, characterized in that, Having the structure shown in formula Ia and / or Ib: (Formula Ia), (Formula Ib), in: M is the resin matrix; A is selected from -O- and -NH-(CH2). t - and -NH(CH2) n NH-, where n is an integer from 2 to 9, and t is an integer from 0 to 9; D1 is a compound containing 1-3 six-membered aromatic rings with a hydroxyl group at the C=O ortho position, and the number of nitrogen atoms in the ring is ≥1; D2 is a compound containing 1-3 six-membered aromatic rings with a hydroxyl group at the ortho position of SO2, and 0-2 nitrogen atoms in the rings; The hydrogens on the six-membered aromatic ring, other than the phenolic hydroxyl hydrogen, are optionally surrounded by one or more hydrogens selected from C1-C2. 20 Alkyl, C6-C 12 Aryl, optional C1-C 20 Substitution of amino, hydroxyl, fluorine and chlorine atoms by substituted groups.

2. The lithium-selective adsorbent according to claim 1, characterized in that, M is selected from any one or more of polystyrene resin, copolymer of styrene and divinylbenzene, phenolic resin, polyacrylic resin, and silicone resin.

3. The lithium selective adsorbent according to claim 1 or 2, characterized in that... D1 has the following structure: 、 、 、 、 、 、 、 、 、 、 , D2 has the following structure: 、 、 、 、 、 、 、 、 、 、 、 、 , * indicates a connection site.

4. The lithium selective adsorbent according to claim 3, characterized in that, It has a structure selected from the following: , , , , , , , , , , , , , , , , , , , , , , , , and , M is selected from polystyrene resin, copolymer of styrene and divinylbenzene, phenolic resin, polyacrylic resin and silicone resin.

5. Use of the lithium selective adsorbent according to any one of claims 1-4 for adsorbing lithium.

6. An extractant for solid-phase extraction of lithium, characterized in that, The lithium-selective adsorbent contains any one of claims 1-4.

7. A method for extracting lithium from sodium-containing brine, characterized in that, The extractant containing the lithium selective adsorbent as described in claim 6 is used, and the initial aqueous phase pH is controlled to be 9-13.5, preferably 10-13.

5.

8. The method according to claim 7, characterized in that, Includes the following steps: S11: The above lithium selective adsorbent is contacted with a lithium-containing sodium solution for extraction, and then solid-liquid separation is performed to obtain lithium-loaded lithium selective adsorbent and raffinate. S12: The lithium-selective adsorbent loaded with lithium is back-extracted using an acid solution and then subjected to solid-liquid separation to obtain the back-extracted adsorbent and the lithium back-extracting solution.

9. The method according to claim 7 or 8, characterized in that, The lithium selective adsorbent is first subjected to alkaline treatment before extraction. Preferably, the adsorbent transformation treatment uses 0.1-1M NaOH solution.

10. The method according to claim 8, characterized in that, The acid solution is selected from sulfuric acid solution and / or hydrochloric acid solution, wherein the concentration of the sulfuric acid solution is 0.5-6 mol / L and the concentration of the hydrochloric acid solution is 1-8 mol / L.

Citation Information

Patent Citations

  • Preparation method of D301 macroporous weekly acidic styrene type anion exchange resin

    CN101781379B